The Role of the State in Creating a Non-Discriminatory Life - Sri Kusriyah; Siti Rhodiyah Dwi Istinah; Ariyani Witasari (Jurnal Hukum Khaira Ummah, 2026)
Conflict, war and bloodshed are impossible to avoid as long as the root of the problem is closely related to the existence of different human beings who cannot be understood by other groups who feel stronger, so that they feel that the presence of different groups must be eliminated, then discriminatory treatment arises, even though the purpose of differences and diversity is actually to respect and appreciate the differences themselves, so what is needed is not a system that tends to eliminate or suppress differences into uniformity, but a system that is able to appreciate and manage differences will be a blessing for all humans. During the New Order era, the government tended to eliminate differences in society by issuing various regulations to create uniformity in social behavior, such as the most prominent ones in the regulation of regional autonomy, political parties and mass organizations, so what happened was a false peace, because society was silenced and there was no access to different opinions, let alone criticize. The confinement of society is not only carried out in the political, legal and economic realms, but also reaches the very sacred area of religion. Religion becomes an area that functions as a tool to perpetuate the power of a regime (status quo), religion does not function as liberation and siding with or protecting the weak, but only as a justification for the legal stamp of the state's desires that are forced on the people. As a result, when the reformation occurred and democratic life began to be opened by President Habibie, it began to appear that friction had occurred in the lives of Indonesian society and violence arose in society with different backgrounds, both ethnicities, groups, classes and even religions which continue to occur until now. The reformation that began rolling in 1998 which wanted a democratic, elegant, civilized, peaceful order of national and state life was only limited to discourse, because what happened was the opposite: ethics and morals were no longer paid attention to, civilization declined, corruption occurred in all lines of life, even to institutions that were considered to be guardians of moral ethics, namely the world of education.